Reviewer acknowledgement - Lossius, Hans Morten (BioMed Central, 2014)
CONTRIBUTING REVIEWERS: The Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine—which received its first Impact Factor in 2013—is extremely grateful for the time, hard work and support of its highly-qualified peer reviewers. The editors of the Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine, the Norwegian Air Ambulance Foundation and BioMed Central would like to show our appreciation by thanking the following people for their assistance reviewing manuscripts for the journal in 2013.